First report of the genus Brachygaster Leach (Hymenoptera: Evaniidae) from India with two new species - Rameshkumar, Anandhan; Huben, Mike R.; Kazmi, Sarfrazul Islam (Zootaxa, 2021)
The genus Brachygaster Leach (Hymenoptera: Evaniidae) is reported from India for the first time and two new species, B. rarum sp. nov. and B. kawadai sp. nov., are described from Maharashtra and Jharkhand. The new species are compared with oriental species viz., B. tschekylli Madl and B. conjugens Enderlein.